Nigeria - Innovative Training for the Improved Delivery of Water - World Bank (Washington, DC, 2012)
The primary objectives of the World Bank-assisted six-year Nigeria National Water Rehabilitation Project (NWRP) are a reliable supply of good quality water, and increased revenue for the country's state water agencies. Nearly 250 urban water systems are being restored to original design capacity. Prior to the start of the project in 1992, many water meters had quit working, valves controlling pipe networks were often faulty, treatment of water was uneven, leaks were often not adequately located and repaired, a number of pumps were not pumping, boreholes were silting up or becoming polluted. All of these deficiencies added up to water systems delivering below design capacity, which in turn resulted in unreliable delivery of water to customers, and revenue often inadequate to enable water agencies to meet basic operational needs, including maintenance of physical assets. The NWRP has effectively changed this situation through an innovative outreach training strategy, an intrinsic part of the institution building and training component which accounted for $ 13 million out of the total project cost of $ 306 million.